Methylated PACs are more potent than their parent compounds: A study of aryl hydrocarbon receptor–mediated activity, degradability, and mixture interactions in the H4IIE‐luc assay. (26th March 2018) - Lam, Monika M.; Bülow, Rebecca; Engwall, Magnus; Giesy, John P.; Larsson, Maria
Abstract: Twenty‐six polycyclic aromatic compounds (PACs; including native polycyclic aromatic hydrocarbons [PAHs], hydroxylated PAHs, alkylated and oxygenated PAHs, and [alkylated] heterocyclic compounds) were investigated for their aryl hydrocarbon receptor (AhR)‐mediated potencies in the H4IIE‐ luc bioassay. Potential degradabilities of PACs were investigated by use of various durations of exposure (24, 48, or 72 h), and various mixtures of PACs including PAHs, alkylated and oxygenated PAHs, and heterocyclic compounds were tested for their joint AhR‐mediated potency. Additive behaviors of PACs in mixtures were studied by comparing observed mixture potencies with mixture potencies predicted by use of the concentration addition model. Methylated derivatives were more potent than their parent compounds in the H4IIE‐ luc assay. A time‐dependent decrease in relative potency was observed for all AhR‐active compounds, which may be indicative of in vitro biotransformation. Monomethylated compounds seemed to be more rapidly transformed than analogous unsubstituted compounds. In addition, the results showed that the predictive power of the concentration addition model increased with the number of compounds, suggesting additivity in multicomponent mixtures. Due to the greater potency of methylated derivatives and their ubiquitous occurrence, there is a need for further research on the toxicity and mixture behavior of these environmentally and toxicologically relevant compounds. Environ Toxicol Chem 2018;37:1409–1419. © 2018 SETAC Abstract : Mixture interactions of polycyclic aromatic compounds in the H4IIE‐ luc assay.